Influence of retrofitting in the seismic behaviour of precast reinforced concrete industrial buildings - Ostetto, Liana (2024)
Previous destructive earthquakes caused large economic losses as well as human losses. Seismic risk studies are of paramount importance to predict the impact of future earthquakes and support seismic risk mitigation policies. The present study presents a seismic risk assessment based on the cost and direct loss assessment of precast industrial buildings with different retrofitting levels in terms of horizontal strength. In this evaluation, a comparative analysis between the configurations of retrofitted buildings and the original building is performed. The effects of retrofitting solution strategies are first investigated in a single building. Then a study is carried out to assess which retrofit solutions level are most appropriate depending on the exposure and seismic risk. The results showed the use of bracing in the PRC building can improve seismic behaviour, with significant increases in horizontal strength. The cost of intervention is reduced, with a slight increase of less than 1% to almost 2% of the cost of the structure. From the derivation of seismic fragility functions for different retrofitting solutions level, the seismic risk analysis with dozens of existing PRC industrial buildings in Portugal points to a large reduction in economic losses as from retrofitted buildings, like an improvement of the seismic capacity of the buildings attributed to the retrofit systems considered. In general, among the different types of retrofit studied, there is an increase in the reduction of total economic losses, namely 49% when retrofitted with a 50% increase in horizontal strength, 58% when retrofitted with a 75% increase in horizontal strength and 64% for retrofitted with 100%.